THE COLONIALITY OF GENDER IN SPORTS AND EDUCATION: COLONIAL LEGACIES OF THE PHILIPPINES’ MODERN GENDER SYSTEM IN ROOKIE (2023) - Pratiwi, Hestia Dwi; Darmoko, Darmoko (UI Scholars Hub, 2025)
This article discusses the lasting impact of colonial-era policies on the gender system portrayed in the Filipino LGBT coming-of-age movie